Energy and cost estimates for separating and capturing CO2 from CO2/H2O using condensation coupled with pressure/vacuum swing adsorption. (1st July 2020) - Lu, Junhui; Cao, Haishan; Li, JunMing
Abstract: Condensation coupled with pressure swing adsorption (CPSA) and condensation coupled with vacuum swing adsorption (CVSA) were used to separate CO2 from CO2 /H2 O mixtures. Six methods are compared using numerical simulations in terms of the energy consumption, separation efficiency and total annual costs for separating CO2 /H2 O mixtures. The effects of inlet CO2 mole fraction, mass flow rate, and pressure on the total annual cost are also studied. A parametric study shows that the total annual costs of all these methods increase as the CO2 mole fraction and mass flow rate increase and decrease with increasing inlet gas pressure. In addition, for CO2 /H2 O mixtures with inlet pressure of 10 kPa, mass flow rate of 40 kg/s, and CO2 mole fraction of 0.1, the average heat rejection of the CPSA processes is higher than that of the CVSA process. Although the CPSA recovery (90.02%) is much lower than that of CVSA (96.26%), the H2 O remove efficiencies of Adsorption for CPSA and CVSA are very close, because that the remained amount of H2 O before Adsorption is very little. A type of CVSA named CcCVSA has the lowest total annual cost with this being the recommended system. Highlights: Condensation coupled with pressure/vacuum swing adsorption was used to separate CO2 /H2 O mixture. Six separation methods are compared in terms of the energy consumption, separation efficiency and total annual costs. The effects of inlet CO2 composition, mass flow rate, and pressure on the total annual cost are studied.